Histoplasmosis : results of the Colombian National Survey, 1992-2008 (2011)
ABSTRACT : Introduction. Histoplasmosis, a fungal disorder characterized by a wide spectrum of manifestations that range from subclinical infections to disseminated processes, affects both immunocompetent and immunosuppressed individuals. Histoplasmosis is not a reportable disease in Colombia and consequently, a survey was designed to collect histoplasmosis cases diagnosed in the country. Objective. The aim of this work was to analyze the data collected from 1992 to 2008. Materials and methods. The survey included demographic data, risk factors, clinical manifestations, imaging data, diagnostic methods and antifungal treatment. Patients were grouped according to risk factors and comparisons of the various findings were done. Results. A total of 434 surveys were gathered from 20 of the country’s Departments. Most patients (96.1%) were adults, 77% were males with a mean age of 38.4 years. Only 3.9% were children less than 15 years of age. In the adult population, AIDS was reported in 70.5% of the cases; additionally, in 7.0% patients other immunosuppressive conditions were informed. The most frequent clinical manifestations were fever (76.1%), cough (54.8%) and constitutional symptoms (56.8%). X rays abnormalities were represented mainly by infiltrates (65.9%) and nodules (17.1%). Diagnosis was made by microscopic observation of H. capsulatum in 49.6% patients, by culture in 58.0% and by serological test in 14.6% cases. Antifungal use was recorded in 52.5% cases. Conclusions. Histoplasmosis is frequent in Colombia, especially in certain risk factor groups such as the HIV-infected population. Data collected from this large number of cases has allowed valid comparisons on various aspects of histoplasmosis in Colombia.